Proceso de atención de enfermería en adultos mayores con neumonía según Virginia Henderson. Hospital Básico Eduardo Montenegro. Enero-abril 2022. - Herrera Muñoz, Yessica Daniela (2022)
The study “NURSING CARE PROCESS IN ELDERLY ADULTS WITH PNEUMONIA ACCORDING TO VIRGINIA HENDERSON. EDUARDO MONTENEGRO BASIC HOSPITAL. JANUARY-APRIL 2022”, research carried out with the objective of developing the nursing care process in older adults with pneumonia according to the Virginia Henderson model at the Eduardo Montenegro Basic Hospital as a tool that promotes effective nursing care, having been defined as descriptive. where qualitative information is handled and the use of documentary sources as well as data from the field study, because the information is collected at a specific time. The project is established as cross-sectional, with a population of 11 nursing professionals in charge of caring for older adults with pneumonia at the Hospital in question, having used the SPSS statistical software for information processing, which facilitated obtaining tables. where it is evident that 40% of the professionals have specialized and handled nursing models including Virginia Henderson's for the design of PAE, at the time of knowing the nursing practice, unsatisfied needs are identified, such as: lack of assessment of inappetence; presence of bad sleeping habits; difficulties or limitations in choosing clothes... elements that supported the need for nursing processes, concluding that the people who work in this nursing home support the investigative processes since they consider they are a contribution to the improvement of services, just as there are weaknesses that can be healed with the use of the proposed PAE, thus improving the quality of health.